МОНИТОРИНГ СОСТОЯНИЯ ПОПУЛЯЦИЙ ОХРАНЯЕМЫХ ВИДОВ РАСТЕНИЙ СЕМЕЙСТВА FABACEAE LINDL. НА ТЕРРИТОРИИ ПЕРМСКОГО КРАЯ - Баландин (Balandin Srgey), Сергей Витальевич (Географический вестник=Geographical bulletin, 2017)
Дается характеристика 6 видов растений семейства Бобовые, входящих в Красную книгу Пермского края. Приводятся параметры изученных популяций, оценивается их состояние. Характеризуется система мониторинга состояния охраняемых видов на территории края и обсуждаются мероприятия по сохранению изученных популяций. MONITORING OF A CONDITION THE POPULATIONS PROTECTED SPECIES OF PLANTS OF FAMILY FABACEAE LINDL. IN TERRITORY OF THEPERMREGION The species’ characteristics of plants of family Fabaceae, which are included in the Red Book of the Perm edge since 2008. They are Astragalus gorczakovskii, Astragalus falcatus, Astragalus glycyphyllos, Oxytropis uralensis, Lathyrus humilis. The monitoring system is the condition of populations of the given species in the territory of the Perm’s edge are as follows: for species of I category 100 % of populations, for II category - 33 %, for III category - 10 % are subject to annual inspection. The condition of all studied populations satisfactory, actions for their preservation is not required.